Understanding family dynamics in adult‐to‐adult living donor liver transplantation decision‐making in Taiwan: Motivation, communication, and ambivalence. Issue 3 (23rd September 2020) - Lin, Ya‐Ping; Chen, Jung; Lee, Wei‐Chen; Chiang, Yang‐Jen; Huang, Chih‐Wan
Abstract : This study investigated how multiple family members co‐construct the ethical significance of living donor liver transplantation (LDLT) and how the family structure and dynamics of donor–recipient–caregiver relationships shape the communication and decision‐making process within the sociocultural context of Taiwan. We conducted in‐depth interviews with 36 participants from 13 families at the Chang Gung Memorial Hospital from February to December 2019. Interviews were audio recorded, transcribed, and translated from Mandarin to English and analyzed utilizing grounded theory and thematic analysis. Our findings revealed that LDLT in Taiwan is not merely a personal choice of either donor or recipient but essentially a collaborative process of family‐centered medical decision‐making, intertwined with socioeconomic conditions, cultural and social norms, gender roles, and the division of labor in the household. The notion of reciprocity and indebtedness for family members is a central theme underlying the entire process of motivation, deliberation, and decision‐making, thereby reinforcing the naturalness of LDLT. However, our study highlighted that donors from families with traditional gender hierarchy and power imbalance may experience psychological and social vulnerabilities. Conclusively, we suggest that healthcare professionals should be sensitive to the contextual and relational factors involved in family dynamics and provide appropriate support to the ambivalent donors. Abstract : Living donor liver transplantation in Taiwan is not merely a personal choice of either donor or recipient but a collaborative process of family‐centered medical decision‐making, intertwined with socioeconomic conditions, cultural and social norms, gender roles, and the division of labor in the household.